System Design for Pose Determination of Spacecraft Using Time-of-Flight Sensors - Wenshan Zhu; Jinzhen Mu; Changbao Shao; Jiaqian Hu; Beichao Wang; Zhongkai Wen; Fei Han; Shuang Li (Space: Science & Technology, 2022)
The pose determination between nanosatellites and the cooperative spacecraft is essential for swarm in-orbit services. Time-of–flight (ToF) sensors are one of the most promising sensors to achieve the tasks. This paper presented an end-to-end assessment of how these sensors were used for pose estimation. First, an embedded system was designed based on the ToF camera with lasers as a driven light source. Gray and depth images were collected to detect and match the cooperative spacecraft in real time, obtaining the pose information. A threshold-based segmentation was proposed to find a small set of the pixels belonging to reflector markers. Only operating on the defined active pixel set reduced computational resources. Then, morphological detection combined with an edge following-based ellipse detection extracted the centroid coordinate of the circular marker, while the center-of-heart rate was calculated as the recognition condition. Next, the marker matching was completed using a deterministic annealing algorithm, obtaining two sets of 3D coordinates. A singular value decomposition (SVD) algorithm estimated the relative pose between the nanosatellite and the spacecraft. In the experiments, the pose calculated by the TOF camera reached an accuracy of 0.13 degrees and 2 mm. It accurately identified the markers and determined the pose, verifying the feasibility of the ToF camera for rendezvous and docking.